Telomere fusions as a signal of term placental aging? A pilot study - Fabiana B Kohlrausch; Fang Wang; Danxia Luo; Rebecca Mahn; David L Keefe (Bioscientifica, 2022)
The placenta plays an essential role at the beginning of life, nourishing and supporting the fetus, but its life span is limited. In late pregnancy, the placenta develops signs of aging, including inflammation and impaired function, which may complicate pregnancy. Placentas also show another sign of aging - cells with extra or missing chromosomes. Chromosomally abnormal cells could gather in the placenta if they get stranded there and/or if the cells do not separate normally. Chromosome separation goes wrong in aging cells when the DNA sequences, which protect the ends of the chromosomes, erode. When chromosomes lose their protective caps, they fuse which leads to abnormal numbers of chromosomes. In this pilot study, for the first time, we found fusions between the caps in a human placenta when it reaches full term. More studies are needed to decide whether this has an influence on how the placenta works and outcomes of pregnancy.